"Dulcor misericordiae". Justicia y misericordia en el ejercicio de la autoridad canónica. I. Historia - Otaduy, Javier (Ius canonicum, 2016)
In the early stages of canon law there was a specific need to intervene to ensure equity in given situations. Canonical equity began to take two forms: perfect justice and benign intervention. These two «souls» have coexisted since the start. Equity encompasses epikeia when the general nature of the law prevents the just appraisal of a specific case. Three representative cases are considered to provide a clearer understanding of the medieval canonical doctrine on aequitas: a letter by St. Augustine in the Decretum Gratiani; a passage from a decretal by Honorius III contained in the Liber Extra; and the great debate between Martinus Gosia and Bulgarus. A number of conclusions as to the ongoing value of equity and some hermeneutical rules relating to its application are drawn on the basis of this discussion.